2023
DOI: 10.1037/fam0001067
|View full text |Cite
|
Sign up to set email alerts
|

Digital location tracking: A preliminary investigation of parents’ use of digital technology to monitor their adolescent’s location.

Abstract: The emergence of digital technologies has changed the dynamic of parent-adolescent relationships. Parents can now use digital technologies to monitor their adolescent's physical location. Yet, to date, no known research has examined the extent to which digital location tracking occurs in parent-adolescent dyads, and how tracking links to adolescent adjustment. The current research examined digital location tracking in a large sample of adolescents (N = 729; M age = 15.03). Overall, about half of parents and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 32 publications
2
3
1
Order By: Relevance
“…We found that White students were overrepresented among current-trackers, whereas participants who identified as Black were overrepresented among never-trackers. This finding differs from the only study of digital location tracking in adolescence (Burnell et al, 2023), which revealed no racial/ethnic differences, and from studies of offline parental monitoring in adolescence, which suggest that non-White parents/caregivers may hold parenting attitudes that encourage more monitoring compared to their White counterparts (Jambunathan et al, 2000;Lansford et al, 2018;Magariño et al, 2021). Our finding is especially surprising given that parents of color endorse the need to maintain safety as a primary motivation for offline monitoring (Sukk & Siibak, 2021), and the highest endorsed motivation for digital location tracking in our sample was for safety.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We found that White students were overrepresented among current-trackers, whereas participants who identified as Black were overrepresented among never-trackers. This finding differs from the only study of digital location tracking in adolescence (Burnell et al, 2023), which revealed no racial/ethnic differences, and from studies of offline parental monitoring in adolescence, which suggest that non-White parents/caregivers may hold parenting attitudes that encourage more monitoring compared to their White counterparts (Jambunathan et al, 2000;Lansford et al, 2018;Magariño et al, 2021). Our finding is especially surprising given that parents of color endorse the need to maintain safety as a primary motivation for offline monitoring (Sukk & Siibak, 2021), and the highest endorsed motivation for digital location tracking in our sample was for safety.…”
Section: Discussioncontrasting
confidence: 99%
“…Digital location tracking was quite common in our sample of community college and 4-year university students, with nearly half of our sample endorsing currently (36.1%) or previously (11.0%) being digitally tracked. This finding is consistent with a representative sample of North Carolina adolescents (aged 12-18 years) collected in 2018, which found that 50% of adolescents' parents digitally tracked their location (Burnell et al, 2023). Inconsistent with previous research suggesting more tracking of female adolescents (Burnell et al, 2023), we found no evidence of gender differences in digital location tracking.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations